The adaptations to strength training: Morphological and neurological contributions to increased strength - Folland, J. P.; Williams, A. G. (Sports Medicine, 2007)
High-resistance strength training (HRST) is one of the most widely practiced forms of physical activity, which is used to enhance athletic performance, augment musculo-skeletal health and alter body aesthetics. Chronic exposure to this type of activity produces marked increases in muscular strength, which are attributed to a range of neurological and morphological adaptations. This review assesses the evidence for these adaptations, their interplay and contribution to enhanced strength and the methodologies employed.